Variability of cork from Portuguese Quercus suber studied by solid-state 13C-NMR and FTIR spectroscopies - Lopes, M. H.; Barros, A. S.; Pascoal Neto, C.; Rutledge, D.; Delgadillo, I.; Gil, A. M. (Biopolymers, 2001)
A new approach is presented for the study of the variability of Portuguese reproduction cork using solid-state 13C-NMR spectroscopy and photoacoustic (PAS) FTIR (FTIR-PAS) spectroscopy combined with chemometrics. Cork samples were collected from 12 different geographical sites, and their 13C-cross-polarization with magic angle spinning (CP/MAS) and FTIR spectra were registered. A large spectral variability among the cork samples was detected by principal component analysis and found to relate to the suberin and carbohydrate contents. This variability was independent of the sample geographical origin but significantly dependent on the cork quality, thus enabling the distinction of cork samples according to the latter property. The suberin content of the cork samples was predicted using multivariate regression models based on the 13C-NMR and FTIR spectra of the samples as reported previously. Finally, the relationship between the variability of the 13C-CP/MAS spectra with that of the FTIR-PAS spectra was studied by outer product analysis. This type of multivariate analysis enabled a clear correlation to be established between the peaks assigned to suberin and carbohydrate in the FTIR spectrum and those appearing in the 13C-CP/MAS spectra. © 2001 John Wiley & Sons, Inc. Biopolymers (Biospectroscopy) 62: 268–277, 2001
The following values have no corresponding Zotero field: publisher: John Wiley & Sons, Inc.
Keywords: 13C-cross-polarization with magic angle spinning; chemometrics; Cork; outer product analysis; photoacoustic FTIR; Quercus suber Linnaeus

Cork suberin as an additive in offset lithographic printing inks - Cordeiro, N.; Blayo, A.; Belgacem, N. M.; Gandini, A.; Pascoal Neto, C.; LeNest, J.-F. (Industrial Crops and Products, 2000)
Suberin oligomers, isolated from cork (Quercus suber L.), were used as additives in ‘Waterless’ and vegetable-oil ink formulations, in the range of 2–10% w:w. The rheological behaviour of the suberin oligomers as well as of the inks, with and without suberin, were investigated as a function of temperature. It was shown that the addition of suberin induces a decrease of viscosity of both inks. The tack of pristine inks, suberin oligomers and their mixtures were determined at different temperatures: the variation of this parameter as a function of time provided information about the drying kinetics of these formulations. The tack of the ‘Waterless’ ink was found to increase with the introduction of suberin, whereas that of vegetable-oil based counterparts decreased. All the trends observed were interpreted in terms of the differences in composition between the two types of inks. Preliminary printing tests were carried out with the various suberin-containing inks
Keywords: Additive; Quercus suber L.; rheological properties; suberin; Tack; Vegetable oil-based ink; Viscosity; Waterless ink

Cork suberin as a new source of chemicals. 1. Isolation and chemical characterization of its composition. - Cordeiro, N.; Belgacem, M. N.; Silvestre, a J.; Pascoal Neto, C.; Gandini, A. (International journal of biological macromolecules, 1998)
Extractive-free cork from Quercus suber L. was submitted to a solvolysis treatment with methanolic NaOH which yielded 37% (o.d. cork) of suberin. This mixture of compounds was thoroughly characterized by FTIR, 1H- and 13C-NMR, gas chromatography coupled with mass spectrometric (GC-MS) analysis, vapour pressure osmometry (VPO), mass spectrography (MS) and gel permeation chromatography (GPC). After derivatization, the main components of the volatile fraction, representing less than half of the total, were found to be omega-hydroxymonocarboxylates, alpha, omega-dicarboxylates, simple alkanoates and 1-alkanols, all with chain lengths ranging from C16 to C24. A second fraction, with an average molecular weight about three times higher, was detected by VPO, MS and GPC. The presence of this important fraction in cork suberin had not been recognized in earlier studies. Both fractions constitute interesting precursors for the elaboration of new materials.
The following values have no corresponding Zotero field: accession-num: 9585884
Keywords: Alkaline methanolysis; Chemical characterization; Cork; Molecular weight distribution; Quercus suber L.; suberin

13C solid-state nuclear magnetic resonance and Fourier transform infrared studies of the thermal decomposition of cork. - Pascoal Neto, C.; Rocha, J.; Gil, A.; Cordeiro, N.; Esculcas, a P.; Rocha, S.; Delgadillo, I.; de Jesus, J. D.; Correia, a J. (Solid state nuclear magnetic resonance, 1995)
The thermal decomposition of cork has been studied by Fourier transform infrared (FTIR) spectroscopy and 13C solid-state nuclear magnetic resonance (NMR) spectroscopy with cross-polarization and magic-angle spinning (CP-MAS), high-power 1H decoupling (HPDEC) and cross-polarization depolarization-polarization (CPDP). Waxes and other soluble components of cork begin to decompose at ca. 150 degrees C. This is accompanied by partial decomposition of suberin, probably initiated at the points of attachment to the cell wall. The carbohydrates begin to decompose at ca. 200 degrees C. The decomposition of lignin begins at 250-300 degrees C, while suberin undergoes further degradation. Significant amounts of coke are formed in the process. At 400 degrees C cork has been transformed into coke with traces of partially decomposed suberin. The thermal decomposition of cork is dependent on the calcination time, particularly in the 200-350 degrees C range.
The following values have no corresponding Zotero field: accession-num: 7773647
Keywords: Fourier Transform Infrared (citation); Hot Temperature; Lignin; Lignin: chemistry; Lipids; Magnetic Resonance Spectroscopy; Membrane Lipids; Membrane Lipids: chemistry; Polysaccharides; Polysaccharides: chemistry; Spectroscopy